Lower Plasma Neuropeptide Y Level in Patients With Atypical Febrile Convulsions - Lung-Chang Lin; Wei-Te Lee; I-Ju Chen; Rei-Cheng Yang (Kaohsiung Journal of Medical Sciences, 2010)
Febrile convulsion (FC) is the most common neurological disease in children. Cases with seizures that persist for more than 15 minutes or recurrent seizures within the same febrile illness are considered to be atypical and may have a different prognosis. Neuropeptide Y (NPY), an endogenous anticonvulsant that is widely distributed throughout the central nervous system, including the hippocampus, is known to prevent seizures by increasing the seizure threshold. Based on our previously finding that patients with atypical FC have lower concentrations of NPY, we hypothesized that the concentration of NPY may play a role in the development of atypical FC. To investigate this hypothesis, we used a radioimmunoassay to measure the plasma NPY concentration of 60 children with FC (typical FC, n = 46; atypical FC, n = 14) and 56 age-matched controls. The atypical FC group had significantly lower concentrations of NPY than children with typical FC and controls (66.47 ± 19.11 pmol/L vs. 88.68 ± 28.50 pmol/L and 86.82 ± 22.66 pmol/L, respectively). Very low NPY levels were found in two patients; one patient (NPY level: 44.75 pmol/L) experienced prolonged seizures lasting for up to 1 hour and the other had recurrent seizures (three seizures) during the same febrile illness (NPY level: 33.53 pmol/L). These results suggest that patients with inadequate NPY inhibitory activity are more susceptible to atypical FC.